A Cross-Sectional Study to Understand 3D Facial Differences in a Population of African Americans and Caucasians - Kau, Chung H.; Wang, Jue; Davis, Matthew (European Journal of Dentistry, 2019)
Objective The purpose of this cross-sectional retrospective study was to use three-dimensional surface imaging to determine gender dimorphism and facial morphological changes from adolescence to adulthood in African American and Caucasian populations.Materials and Methods Three-dimensional images were captured and the total sample size included 371 subjects. Images were combined using Rapidform 2006 Plus Pack 2 software to produce a male and female facial average for each population. Comparisons were conducted within the following categories: (1) gender comparison within each race, (2) adult and adolescent comparison within each race, and (3) adult and adolescent comparison between the races.Results Adolescent gender comparisons within each race showed high percentages of similarity. However, adult females in both races showed more prominent periorbital, malar, and nasolabial regions and less prominent lower forehead, nose, and lower face compared with adult males of the same race. African American adult females showed increase in length and width of the face, increased nasal tip projection, and decreased periorbital regions compared with African American adolescent females. Welsh adult females had an increase in the nose and chin projection compared with Welsh adolescent females. Adult males of both races had increase in nose and chin projection, increase in length and width of the face, and decreased periorbital, malar, and nasolabial regions compared with adolescent males of the same race. African American adolescents had a wider alar base, more protrusive lips, and periorbital regions, and less prominent nose and chin compared with the Welsh adolescents. African American adults also had a wider alar base; more protrusive lips and periorbital regions; a broader face; and more retrusive chin, nose, nasolabial region; and lower forehead compared with Welsh adults.Conclusions Few differences were noted between genders within the same racial groups during adolescence. However, changes became more distinct in adulthood. From adolescence to adulthood, facial morphologies were similarly matched within the gender for females; however, there were significant changes for males. Lastly, facial morphology patterns tend to be established early in life.
Keywords: 3D faces; 3D imaging; orthodontics